Markov Chain Monte Carlo Simulation Methods for Structural Reliability Analysis. (2017) - Proppe, Carsten
Abstract: Two Markov chain Monte Carlo simulation methods for reliability estimation, subset simulation and the moving particles algorithm, are compared. To this end, both low-dimensional and high-dimensional test cases are considered. The investigation sheds light on the avoidance of correlated samples in both algorithms, notably on the necessity of a burn-in period and the influence of a metamodel.